Maternal Working Hours and the Well-Being of Adolescent Children - Silvia Mendolia (Institute for the Study of Labor (IZA), 2014)
This study investigates how maternal working hours are related to various outcomes in children aged 11 to 15 using a sample of mothers and adolescents in the British Household Panel Survey. Research that examines the effects of maternal employment on children has been motivated by the rapid increase of female participation rates in the labour market and increased shares of children living in female-headed or single-mother households. The existing literature on this issue is very limited, mostly based on American data, and provides conflicting results. Fixed effects have been used in the present analysis to control for characteristics of children and families that do not vary over time. The results suggest that full-time maternal employment (as opposed to part-time) has little or no effect on the propensity of adolescents to smoke, their life satisfaction, self-esteem, or intention to leave school at 16. These results are stable and consistent across various specifications of the model and different socio-economic status.
Keywords: I10; J13; J22; 330; maternal working hours; adolescent well-being; children smoking